Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a> c1: \(=1-\sqrt{x^3}=1-\sqrt{x^2.x}=1-x\sqrt{x}\)
c2 \(=1+\sqrt{x}+x-\sqrt{x}-x-x\sqrt{x}=1-x\sqrt{x}\)
b> c1: \(=\sqrt{x}\left(4-\sqrt{2}\right)\sqrt{x-\sqrt{2x}=\sqrt{x\left(x-\sqrt{2x}\right)}}\left(4-\sqrt{2}\right)\)
c2: \(=4\sqrt{x\left(x-\sqrt{2x}\right)}-\sqrt{2x\left(x-\sqrt{2x}\right)}=\sqrt{x\left(x-\sqrt{2x}\right)}\left(4-\sqrt{2}\right)\)
a)\(\left(1-\sqrt{x}\right)\left(1+\sqrt{x}+x\right)=1-\sqrt{x^3}\)
b) \(\left(\sqrt{x}+2\right)\left(x-2\sqrt{x}+4\right)=\sqrt{x^3}+8\)
c)\(\left(\sqrt{x}-\sqrt{y}\right)\left(x+y+\sqrt{xy}\right)=\sqrt{x^3}-\sqrt{y^3}\)
d)\(\left(x+\sqrt{y}\right)\left(x^2+y-x\sqrt{y}\right)=x^3+\sqrt{y^3}\)
Giải:
a) \(\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)\)
\(=\left(\sqrt{x}\right)^3-1\)
Vậy ...
b) \(\left(\sqrt{x}+\sqrt{y}\right)\left(x-\sqrt{xy}+y\right)\)
\(=\left(\sqrt{x}\right)^3+\left(\sqrt{y}\right)^3\)
Vậy ...
c) \(\left(2\sqrt{x}+\sqrt{y}\right)\left(3\sqrt{x}-2\sqrt{y}\right)\)
\(=6x+3\sqrt{xy}-4\sqrt{xy}-2y\)
\(=6x-\sqrt{xy}-2y\)
Vậy ...
\(a.\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)=x\sqrt{x}-1\)
\(b.\left(\sqrt{x}+\sqrt{y}\right)\left(x-\sqrt{xy}+y\right)=x\sqrt{x}+y\sqrt{y}\)
\(c.\left(2\sqrt{x}+\sqrt{y}\right)\left(3\sqrt{x}-2\sqrt{y}\right)=6x-\sqrt{xy}-2y\)
\(A=\left\{\frac{2\sqrt{xy}\left(\sqrt{x}+\sqrt{y}\right)}{\sqrt{x}+\sqrt{y}}+\frac{\sqrt{x}\left(x+y\right)}{\sqrt{x}}\right\}.\left(\frac{\sqrt{x}-\sqrt{y}}{\left(\sqrt{x}+\sqrt{y}\right)\left(\sqrt{x}-\sqrt{y}\right)}\right)^2.\)
=> \(A=\left(2\sqrt{xy}+x+y\right).\frac{1}{\left(\sqrt{x}+\sqrt{y}\right)^2}\)
=> \(A=\frac{\left(\sqrt{x}+\sqrt{y}\right)^2}{\left(\sqrt{x}+\sqrt{y}\right)^2}=1\)
ĐS: A=1
\(a,\left(4\sqrt{x}-\sqrt{2x}\right)\left(\sqrt{x}-\sqrt{2x}\right)=4x-4\sqrt{2}x-\sqrt{2}x+2x=6x-5\sqrt{2}x=\left(6-5\sqrt{2}\right)x\)
\(b,\left(2\sqrt{x}+\sqrt{y}\right)\left(3\sqrt{x}-2\sqrt{y}\right)=6x-4\sqrt{xy}+3\sqrt{xy}-2y=6x-4\sqrt{xy}-2y\)
a/ 6x
b/ 6x-2y-\(\sqrt{xy}\)